Neuroscience of Meditation - Vinod D. Deshmukh (The Scientific World Journal)
Dhyana-Yoga is a Sanskrit word for the ancient discipline of meditation, as a means to Samadhi or enlightenment. Samadhi is a self-absorptive, adaptive state with realization of ones being in harmony with reality. It is unitive, undifferentiated, reality-consciousness, an essential being, which can only be experienced by spontaneous intuition and self-understanding. Modern neuroscience can help us to better understand Dhyana-Yoga. This article discusses topics including brain-mind-reality, consciousness, attention, emotional intelligence, sense of self, meditative mind, and meditative brain. A new hypothesis is proposed for a better understanding of the meditative mind. Meditation is an art of being serene and alert in the present moment, instead of constantly struggling to change or to become. It is an art of efficient management of attentional energy with total engagement (poornata, presence, mindfulness) or disengagement (shunyata, silence, emptiness). In both states, there is an experience of spontaneous unity with no sense of situational interactive self or personal time. It is a simultaneous, participatory consciousness rather than a dualistic, sequential attentiveness. There is a natural sense of well being with self-understanding, spontaneous joy, serenity, freedom, and self-fulfillment. It is where the ultimate pursuit of happiness and the search for meaning of life resolve. One realizes the truth of ones harmonious being in nature and nature in oneself. It is being alive at its fullest, when each conscious moment becomes a dynamic process of discovery and continuous learning of the ever-new unfolding reality.